Factors Affecting Vehicle Purchase in Major Cities - Shrestha, Sajeeb Kumar (The EFFORTS, Journal of Education and Research, 2022)
Nowadays, personal vehicles have become synonymous with the modern city market. The development and splendor of the city can also portray by the use of such vehicles. The purpose of this study was to analyze the factors affecting vehicle buying in major cities. This research used descriptive and causal research design. Primary data were collected. Survey research was administered and 2000 responses were collected. A PLS-SEM tool was used to test validity, reliability and path of advance modeling. This research confirmed expected features, price, dealer/showroom influence has significant influence on car buying. After sales service has no effect on car buying. Marketers should identify target group who showed interest on cars and marketing programs should be directed to them.